(untitled) (Oratio Directa, 2019)
This literature review examines the relationship between press systems and the development of internet media. It explains the foundations of press systems, changes in media forms resulting from digitalization, and the functions of the press in delivering information through online media. The discussion applies a descriptive-conceptual reading of literature on mass communication, press systems, electronic media, and new media. The review shows that internet media expand the production, distribution, and accessibility of information, while journalistic principles, social responsibility, and press independence remain necessary. The relationship between press systems and internet media is therefore not merely technological; it is also shaped by informative, supervisory, interpretive, educational, economic, and citizens' rights functions.